KREATIVITAS ELA MUTIARA DALAM TARI KANYA - Kusumadewi, Murtisa Sulistin (Jurnal Ilmu Budaya, 2020)
Kanya is a contemporary dance that raises the issue of early marriage in Sukabumi. This study uses a qualitative method with a descriptive analysis approach that provides a description or description by describing data obtained from the field regarding the choreography of the Kanya dance, as well as Ela's creativity in compiling the Kanya dance. To answer the problem regarding the Kanya dance choreography, it was explained using the basic elements of choreography based on Sumandiyo Hadi's opinion. In addition, Ela's creativity was explained using the 4P concept proposed by Rhodes, namely (1) person (2) press (3) process (4) product. The results obtained from Ela's study of creativity in the Kanya dance work were greatly influenced by her experience as a dancer and choreographer. This creativity is manifested in daily motives by the lack of a stilator and a combination of techniques such as fibration, fall and recovery, repetition, and tempo adjustment. The conclusion of this research is the result of Ela's creativity that uses daily movements by exploring the characteristics of some rope and jug characteristics as well as minimalist clothing and make-up choices.